2005
DOI: 10.1007/s00259-005-1812-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of 18F-FDG and 99mTc-depreotide SPECT in the diagnosis of malignancy of solitary pulmonary nodules

Abstract: This study showed( 18)F-FDG PET to be more sensitive than ( 99m)Tc-depreotide SPECT in the diagnosis of malignancy of SPNs. However, the combination of both techniques may provide additional accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 22 publications
1
42
0
Order By: Relevance
“…Moreover the precise mechanism of depreotide uptake in tumour cells is not completely clear, and there is an ongoing debate about whether this is due to somatostatin receptors on tumour cells or to tumour-infiltrating lymphocytes [9] . The evidence of somatostatin receptors in non-small cell lung cancer cells is still controversial, while there are no data regarding their expression profile in adenocarcinomas [8] that some authors reported to be falsely negative in depreotide tests [8,10] . A potential advantage of SPECT over PET could be the higher accuracy in detecting carcinoid tumours that may not be detectable at FDG-PET scan, but the major diagnostic problem in the evaluation of SPN concerns the identification of lesions !…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover the precise mechanism of depreotide uptake in tumour cells is not completely clear, and there is an ongoing debate about whether this is due to somatostatin receptors on tumour cells or to tumour-infiltrating lymphocytes [9] . The evidence of somatostatin receptors in non-small cell lung cancer cells is still controversial, while there are no data regarding their expression profile in adenocarcinomas [8] that some authors reported to be falsely negative in depreotide tests [8,10] . A potential advantage of SPECT over PET could be the higher accuracy in detecting carcinoid tumours that may not be detectable at FDG-PET scan, but the major diagnostic problem in the evaluation of SPN concerns the identification of lesions !…”
mentioning
confidence: 99%
“…This technique is based on a somatostatin analogue (depreotide) scintigraphy. A recent paper by Halley et al [8] Tc-depreotide SPECT were found to be equally sensitive (92.3%) for large and equally specific (85.7%) for small SPNs. The reported higher sensitivity of FDG-PET in small-size ( !…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Solitary pulmonary nodules (SPNs) are single, spherical, well-circumscribed, radiographic opacity that measures ≤ 3 cm in diameter. Provided a visually validated diagnostics of the SPNs in PET images, these studies [339][340][341][342][343][344][345][346] have reported an SPN diagnostic accuracy with a sensitivity of 88-96% and a specificity of 70-90% for malignant cells (see Table 9 for more detail).…”
Section: Pet/ct Nodule Diagnosismentioning
confidence: 99%
“…In PET images, the malignant cells have unregulated metabolism that results in having higher FDG uptake that permits malignancy to be detected. Reported studies [339][340][341][342][343][344][345][346] used this characteristic to detect malignant solitary pulmonary nodules (SPNs) in PET. Solitary pulmonary nodules (SPNs) are single, spherical, well-circumscribed, radiographic opacity that measures ≤ 3 cm in diameter.…”
Section: Pet/ct Nodule Diagnosismentioning
confidence: 99%